Hazardous Household Substances: Alternatives That Are Relatively Free of Toxic Effects - Marie Hammer (EDIS)
This document is FCS 3149, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002. First published: June 1988. Revised: July 2002.